Tapentadol PR for Pain Syndromes in Real Life Patients with Hematological Malignancy - A. Brunetti, Gregorio; Palumbo, Giovanna; S. Morano, Giacomo; Baldacci, Erminia; Carmosino, Ida; Annechini, Giorgia; Talone, Romina; Kiflom, Sara; Mastrogiacomo, Giada; Grammatico, Sara; Chisini, Marta; Costa, Adriana; et al. (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2016)
Background: More than 50% of oncohematological patients suffer from pain syndrome, mostly originating from the bone, which often include nociceptive and neuropathic complaints. Tapentadol, a recently available treatment option for cancer pain, exerts a dual analgesic mechanisms (opioid and noradrenergic), allowing for a high clinical efficacy as well as for a reduction in adverse events compared to traditional opioids. Aim: To explore the safety and efficacy of tapentadol as a suitable agent for the pain management in the setting of oncohematology. Methods: Our observational study included 36 patients with basal pain intensity (NRS) ranging from 5 to 10. Tapentadol prolonged release (PR) was given at the initial dose of 50 mg BID and careful titrated according to the achieved pain control. Results. Tapentadol PR was given at the dosages ranging from 200 and 260 mg/day after a careful titration, allowed for a clinically (-7 points NRS) remarkable reduction of pain intensity without any significant side effects. Conclusion: In oncohematological patients on pain, tapentadol PR was effective and well tolerated, so representing a suitable treatment option in this difficult setting.
Keywords: syndromes